Teologie en die debat oor ’n hermeneutiek vir menseregte - Du Toit, SF (Nederduitse Gereformeerde Teologiese Tydskrif, 2004)
Theology and the debate on human rights hermeneutics Human rights hermeneutics is facing a crisis on several fronts. Exacerbated by conflict in many parts of the world, the impasse between universalists and relativists seems to be deepening. However, a human rights hermeneutics grounded in dialogue, appears to offer an escape route from this ideological cul-de-sac. South Africa’s political transition from apartheid to democracy, it seems, presents a case in point. Dialogue between a number of partners helped to shape a human rights package that was taken up in a mutually acceptable Constitution, and helped to find a way to deal with a violent past. One (often- neglected) partner in the dialogue with the human rights tradition was Reformed theology. Looking back, this mutually-enriching conversation introduced Reformed theology in South Africa to conversations beyond the parochialism of Afrikaner Nationalism, and thus offered a liberating possibility. Conversely, theology, along with many other partners, helped to shape the human rights discourse in South Africa, firstly, by offering a nuanced anthropology on which to base reconciliation and subsequent development efforts. Secondly, theology helped to combine individual, social and ecological rights in an integrated development project. Thirdly, theology brought to the table a focus on marginalized voices. I conclude that these characteristics illustrate how, despite dialogue, inclusivity and compromise, South Africa averted the relativisation of non-derogable human rights.